The Role of Islamic Religious Education Teachers in the Formation of Good Morals during the Covid-19 Pandemic at SMP IT Al-Asror - Yunia Eka Putri; Nurul Fauziah; Lisnawati; Joko Supriyanto; Rudi Kurniawan; Kalimatus Saroh; Latifah; Muhammad Iqbaludin; Mamlu'atul Khoiru Nisa; Irham Zaini Mubarok (Bulletin of Science Education, 2023)
The aim of this study is to explore the role of PAI teachers in shaping students' moral character during the COVID-19 pandemic at SMP IT Al-Asror, Sumbersari Village, Sekampung District, East Lampung Regency, as well as to identify the supporting and inhibiting factors involved in this process. This research employs a qualitative approach. The informants include the school principal, teaching staff, parents, and students. Data collection techniques used are observation, interviews, and documentation. The validity of the data is ensured through triangulation of methods and sources. Data analysis follows the Miles and Huberman model, which involves data reduction, data presentation, and drawing conclusions. The results of the study reveal that PAI teachers played a significant role in developing students' moral character during the pandemic through collaboration with parents regarding students' learning discipline at home, mandatory prayers, completion of assignments, and students' attitudes toward their families and surroundings. The supporting factors include: (1) the role of parents or guardians, (2) advancements in technology, and (3) the use of social media. The inhibiting factors include poor internet connection, students' personal attitudes, the role of parents or guardians, lack of behavioral supervision at home, and students' laziness in completing assignments. Keywords: Good Morals, Religious Education Teachers, and Inhibiting Factors